Teaching self-regulation through role modeling in K-12 - Adıgüzel, Tufan; Aşık, Gürsu; Bulut, Mehmet Akın; Kaya, Mehmet Haldun; Özel, Serkan (Frontiers in Education, 2023)
This mixed-method case study reveals the implications of a specially designed professional development program for in-service K-12 teachers. The program aimed to teach how to promote self-regulated learning skills through role modeling strategy to participant teachers. The quantitative data were obtained from the participant teachers' lesson plans using the rubric developed by the researchers. Qualitative data were obtained from a theoretical thematic analysis of the lesson plans, expert feedback, and online student products. The findings showed that (a) teachers act as agents to improve students’ self-regulated learning skills through role modeling, (b) role modeling functions as a key to learning-centered lessons, and (c) role modeling strategy can be used to integrate various self-regulated learning skills into a lesson.